Srebf1a is a key regulator of transcriptional control for adipogenesis - Ayala-Sumuano, Jorge-Tonatiuh (Nature Publishing Group, 2011)
Adipogenesis is regulated by a complex cascade of transcriptional factors, but little is known about the early events that regulate the adipogenic program. Here, we report the role of the srebf1a gene in the differentiation of fibroblastic 3T3-F442A cells. We found that expression of srebf1a depended on GSK3β activity and that GSK3β activity was necessary for C/EBPβ phosphorylation at Thr188. Knockdown of srebf1a inhibited the adipogenic program because it blocked the expression of genes encoding PPARγ2, C/EBPα, SREBP1c and even FABP4, demonstrating that SREBP1a activation is upstream of these three essential adipogenic transcription factors. Kinetic analysis during differentiation illustrated that the order of expression of adipogenic genes was the following: cebpb, srebf1a, pparg2, cebpa, srebp1c and fabp4. Our data suggest that srebf1a acts as an essential link between the GSK3β-C/EBPβ signaling axis and the beginning of the adipogenic transcriptional cascade.